Fast photoacoustic-guided depth-resolved Raman spectroscopy: a feasibility study - Gao, Fei (2016)
In this Letter, photoacoustic-guided Raman spectroscopy (PARS) is proposed for a fast depth-resolved Raman measurement with accurate depth localization. The approach was experimentally demonstrated to receive both photoacoustic and Raman signals from a three-layer agar phantom based on a developed synergic photoacoustic-Raman probe, showing strong depth correlation and achieving magnitude of faster operation speed due to photoacoustic time-of-flight measurement and guidance, compared with the conventional depth-resolved Raman spectroscopy method. In addition, further combination with advanced optical-focusing techniques in biological-scattering medium could potentially enable the proposed approach for cancer diagnostics with both tight and fast optical focusing at the desired depth of tumor.